The Correlation Between Processing Skills and Learning Outcomes Based on Implementation Discovery Learning - Muhamad Rozak Hidayat; Fatikhatun Nikmatus Sholihah (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
This research is a classroom action research that aims to determine the relationship between process skills and student learning outcomes in the Discovery Learning model of learning biology material for the respiratory system class XI MIA. This research is a type of quantitative research using the One Shot Case Study research method. The subjects in this study were all students of class XI MIA MA Nizhamiyah ploso, totaling 14 students. Data collection techniques are by observation, interviews, and questionnaires. Assessment instruments using questionnaires and questions in the form of multiple choice. While data analysis with correlation test using SPSS. The average value of cognitive learning outcomes obtained by MA students in class XI Nizhamiyah Ploso through the application of discovery learning models assisted by Student Worksheet Media is 73.5714, which means the average value obtained by students is in the good category. And the average value of the results of the process skills of MA class XI Nizhamiyah Ploso students by applying the discovery learning model with the help of YouTube in the form of practicum for making respiratory system props produced an average number of 83.3571 with the number of samples used, namely 14 students. class XI MIA. The average value of learning outcomes on learning outcomes is 73.5714 < 82.3571 skills, so it can be interpreted descriptively that there is a difference in the average learning outcomes of students between cognitive learning outcomes and process skills. Based on the results of the calculation of Normality, Homogeneity and correlation test, it shows that there is a relationship between cognitive learning outcomes and the process skills of Biology students of class XI MIA MA Nizhamiyah Ploso.